Rancangan Morfologi Bahasa Suku Anak Dalam Jambi Sebagai Buku Ajar Muatan Lokal - Kamarudin Kamarudin (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2018)
This study aims to describe and design a language morphology Suku Anak Dalam (BSAD) into a textbook. Research conducted at the Batanghari Bungku Jambi. This study used a qualitative approach. The research subject BSAD speakers. Data collection techniques using literature techniques, record, note. Data were analyzed using a unified and agih. Data validation is done by extending and triangulation. The results showed language Suku Anak Dalam own; (1) morpheme, namely; free morpheme and morpheme, (2) the morphological form of pengimbuhan and looping, (3) the form of prefixes morfofenemis mәN- and pәN-. (4) class in the form of words; verbs, adjectives and nouns. Based on the results of the study of language Suku Anak Dalam above it can be designed textbook morphology language Suku Anak Dalam consisting of: (1) the preface, (2) content, (3) the torso is composed of chapters, subchapters, as well as instructional objectives , (4) references, (5) a glossary, and (6) Index. Keywords: Morphology, Textbook